2020
DOI: 10.3390/pathogens9110965
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 as a Trigger of Recurrent Guillain–Barré Syndrome

Abstract: Coronavirus 2019 (COVID-19) has been reported to trigger Guillain–Barré syndrome (GBS). While uncommon, recurrent GBS (rGBS) episodes, triggered by antecedent viral infections, have been reported in a small proportion of GBS patients, here we describe a patient with a recurrent case of GBS, occurring secondary to COVID-19 infection. Before this patient’s episode, he had two prior GBS flares, each precipitated by a viral infection followed by complete recovery besides intermittent paresthesias. We also consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
1
13
0
3
Order By: Relevance
“…A case of recurrent GBS, occurring secondary to COVID-19 infection, has also been described, wherein the patient had two prior flares of GBS, each episode being precipitated by a viral illness followed by complete recovery and a recent event following COVID-19 infection. 2 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A case of recurrent GBS, occurring secondary to COVID-19 infection, has also been described, wherein the patient had two prior flares of GBS, each episode being precipitated by a viral illness followed by complete recovery and a recent event following COVID-19 infection. 2 …”
Section: Discussionmentioning
confidence: 99%
“…1 A case of recurrent GBS, occurring secondary to COVID-19 infection, has also been described, wherein the patient had two prior flares of GBS, each episode being precipitated by a viral illness followed by complete recovery and a recent event following COVID-19 infection. 2 CIDP is a relapsing-remitting or progressive inflammatory demyelinating polyneuropathy, which has a varied clinical presentation. CIDP can be a challenging diagnosis for physicians due to the heterogeneity of presentations, ranging from distal versus proximal onset, symmetric versus asymmetric onset and sensory versus motor variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After thorough literature review, we found a substantial number of reported cases and case series of Covid-19 infection presented with GBS. Table 1 summarizes demographic, type of relationship with Covid-19, clinical and GBS sub-types, response to specific GBS treatment, and outcome of different GBS cases who presented in concurrent with Covid 19 infection [[ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ],[ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ...…”
Section: Discussionmentioning
confidence: 99%
“…Common neurological symptoms of COVID-19 are headache, dizziness, dysgeusia/ageusia, hyposmia/anosmia, seizure, stroke, and encephalopathy [ 2 ]. There have been reported cases of Guillain-Barré Syndrome (GBS) associated with COVID-19 from different parts of the world [[ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ],[ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ,…”
Section: Introductionmentioning
confidence: 99%